Mandatory Corporate Social Responsibility Explanation - Prasetio , Januar Eko; Sabihaini , Sabihaini; Bintarto, Bambang; Susanto , Anindyo Aji; Rahmanda, Gita Astyka (RSF Conference Series: Business, Management and Social Sciences, 2021)
This article describes the development of the implementation of Corporate Social Responsibility (CSR) around the world from several CSR published works. The development of global CSR implementation starts voluntary to mandatory. Based on the discussion, CSR is an obligation (mandatory) for companies in carrying out company operations and is part of the company’s investment. Thus its benefits can be enjoyed by the company in the long term.